Financial Management: Foundations and Contemporary Challenges - Alshehri, Ruwaida Saeed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study, titled "Financial Management: Foundations and Contemporary Challenges," addresses the challenges faced by organizations due to rapid economic and technological changes. The research aims to explore how these challenges impact financial management strategies and enhance the understanding of modern practices in this field. A descriptive analytical methodology was employed for data collection, utilizing surveys distributed to 20 financial management professionals from various sectors, including banking, manufacturing, and services. The surveys included questions about contemporary challenges, financial management strategies, and the outcomes of these strategies. Data were analyzed using statistical methods such as frequency analysis and regression to examine the relationships among different variables. The results indicated that 84.2% of participants believe that effective financial management strategies enhance organizational performance, reflecting the importance of financial planning in achieving institutional goals. Additionally, 73.7% reported that their organizations adopt flexible strategies to adapt to rapid changes in the economic environment. Furthermore, 60% of participants acknowledged the significance of modern technologies, such as advanced analytics and artificial intelligence, in improving financial efficiency and increasing competitive advantage. The conclusions highlight the need to develop flexible financial strategies and innovative technological tools to enhance organizations' ability to adapt to ongoing challenges. They also emphasize the importance of investing in employee training and regularly updating financial plans to ensure effective responses to changes. These findings underscore the vital role of financial management as a key factor in achieving sustainability and organizational success in a rapidly changing environment, providing a practical framework for effective financial practices.
Keywords: financial management; competitiveness; institutional challenges; economic changes; financial planning; financial management strategies